The Kinds Of Characters Portrayed In Friendship Film - Nikhael Okita Dawad Singal; Gek Wulan Novi Utami; I Nyoman Tri Ediwan (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study analyses the types of characters depicted in the 2024 film Friendship, directed by Andrew DeYoung, through the lens of E.M. Forster's character classification theory, specifically the distinction between flat and round characters. Using a qualitative content analysis approach, this research explores how these characters are constructed and developed throughout the film, as well as how they contribute to the emotional and thematic depth of the narrative. The film Friendship presents a dark yet psychologically rich exploration of modern masculinity, male loneliness, and emotional repression. The research findings indicate that the characters Craig Waterman and Austin Carmichael are round characters, exhibiting emotional complexity, inner conflict, and character development. On the other hand, Tami Waterman, Steven Waterman, and Tony are flat characters, remaining emotionally static and serving specific narrative purposes without significant transformation. This analysis highlights how character depth shapes viewers' understanding of social and psychological themes, particularly in contemporary cinematic narratives.